المستشرق البولوني تادايوش ليفيتسكي…والتراث الإباضي - بسكر, محمد (البصائر, 2020)
أ. محمد بسكر / انبعاث التاريخ من خلال المخطوطات سمة مميزة للأبحاث التاريخية التي وضعها المستشرقون ال
Keywords: Orientalisme -- Pologne

Polish Travellers in Libya - Jarecka-Stepien, Katarzyna (The Maghreb Review, 2006)
Keywords: Orientalisme -- Pologne; Récits de voyage -- Djebel Nefousa

Qirā’a fī K. Dirāsāt Shimāl Ifrīqiyya li’l-Mustamzigh al-Būlandī Līfītskī - Rabīʿ, Muḥammad (2006)
Keywords: Orientalisme -- Pologne

Tadeusz Lewicki’s Academic Achievements in the Field of African Studies - Kłosowicz, Robert (Pioneers of African Studies in Krakow. In memory of Professor Roman Stopa (1895-1995), 2019)
Keywords: Orientalisme -- Pologne